The Qur'an's Thematic Approach to Water Fiqh as a Pillar of Environmental Ethics towards Sustainable Theological Ecological Development - Syakira, Syakira (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This research aims to examine the concept of water in the Qur'an through a thematic interpretation approach and relate it to water fiqh as the basis for the formation of environmental ethics towards sustainable theological ecological development. Water is understood not only as a natural resource that sustains life, but also as a divine mandate that contains theological, moral, and legal dimensions. This understanding is important in the midst of a contemporary ecological crisis characterized by water scarcity, environmental pollution, and uncontrolled exploitation of natural resources. This research uses a qualitative method with a literature study design. The research data is in the form of Qur'anic verses related to water, especially Q.S. al-Anbiyā' [21]:30, Q.S. al-Wāqi'ah [56]:68–70, and Q.S. al Mulk [67]:30, and is supported by two main literature that discusses Islamic environmental ethics and fiqh al-bi'ah. The data was analyzed using the thematic interpretation method to identify the pattern of the meaning of the verses about water, then analyzed descriptively to map its relationship with the principles of environmental fiqh. The results of the study show that the Qur'an consistently displays water as the source of life, the gift of Allah that is beyond the full control of humans, as well as entities that can experience crises as a form of theological warning against human behavior. These findings are in line with the Islamic framework of environmental ethics and the principles of fiqh al-bi'ah which emphasize responsibility, ecological justice, and the prohibition of environmental damage. This study concludes that the integration of thematic interpretation of the Qur'an and water fiqh makes an important contribution to the development of a sustainability-oriented theological ecology, while enriching the treasures of contemporary Islamic interpretation and fiqh studies in responding to global ecological problems.